Conduction Abnormality and Arrhythmia After Transcatheter Closure of Atrial Septal Defect - Mleczko, Szymon; Olszowska, Maria; Sobień, Bartosz; Komar, Monika; Podolec, Piotr; Tomkiewicz-Pająk, Lidia; Stępniewski, Jakub; Przewłocki, Tadeusz; Podolec, Jakub; Żmudka, Krzysztof (Circulation Journal, 2014)
Background:The aim of this study was to prospectively perform ambulatory 24-h ECG monitoring to assess the effects of transcatheter closure of atrial septal defect (ASD).Methods and Results:A total of 235 consecutive subjects (female, n=163; male, n=72; age, 44.6±14.4 years) were enrolled in the study, who were due undergo ASD closure. Holter monitoring was performed before procedure and at 1, 6 and 12 months of follow-up. During the procedure transient supraventricular arrhythmia occurred in 8 patients (3.4%), and bradycardia in 3 (1.3%). In 3 patients (1.3%) an episode of atrial fibrillation occurred in the first hour after the procedure. In 8 patients (3.4%) transient first-degree atrioventricular block was noted. A significant increase in number of supraventricular extrasystoles (SVES)/24 h was noted 1 month after the procedure (P<0.001). On multiple forward stepwise regression analysis, device size and fluoroscopy time had an influence on increase in number of SVES seen 1 month after the procedure (P<0.001).Conclusions:Transcatheter closure of ASD is associated with a transient increase in supraventricular premature beats and a small risk of conduction abnormalities and paroxysmal atrial fibrillation in early follow-up. Transcatheter closure of ASD does not reduce arrhythmia that appears prior to ASD closure. Larger device size and longer procedure time are associated with increased risk of supraventricular arrhythmia on early follow-up. (Circ J 2014; 78: 2415–2421)